Lawyers and the Lies They Tell - Bruce A. Green; Rebecca Roiphe (Washington University Journal of Law and Policy, 2022)
The law holds lawyers to a more demanding standard of conduct than others when it comes to aspects of their fiduciary relationships with courts and clients. For instance, states can sanction lawyers for some speech inside a courtroom that would be protected if uttered by a non-lawyer. This Article explores whether lawyers’ free speech rights should also be different from those of other speakers when lawyers, acting on their own behalf, participate in political discourse. Applying the current First Amendment framework, the authors question the bar’s assumption that, simply because lawyers are subject to rules of professional conduct, courts can regulate lawyers’ speech outside the practice of law more restrictively than the state regulates others’ speech. The authors disagree with the premise that lawyers do not deserve the same robust protection for disfavored political speech afforded to political speakers in general. Ultimately, the Article argues that the First Amendment calls for strict scrutiny of professional conduct rules subjecting lawyers to punishment for lying in the public media on subjects of political concern. On rare occasions, applying the rules can be justified under this standard of review. However, when lawyers, acting in their private capacity, tell political lies to the public, the rules will often fail to closely serve an important state interest as required to satisfy this standard.
Keywords: Lawyers; Ethics; Professional; Conduct; Rules; First Amendment; Constitution; Professional conduct; Rules of conduct; Free speech; Rights; political speech; Disfavored; Protection; Public media; Private capacity; Political lies; Lies; dishonesty; Professional standards; Speakers; public